Response of LiF:Mg,Cu,P TL detector simulated with Geant4 - Supian Samat; W. Priharti (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Geant4 simulation code was developed to study the Hp(10) energy response of the LiF:Mg,Cu,P (TLD-100H). Initial study chose the simulation conditions similar to the work reported by Obryk et al. in year 2011, in which a TLD-100H chip without filter was used. The work went further to simulate the Hp(10) results obtained experimentally at SSDL Malaysia. The experiment used a TLD-100H chip embedded in a TLD card and the card was enclosed in a badge complete with PTFE filter. Irradiation with eleven photon energies in the range of 24-1250 keV was applied. The simulation code therefore took into accounts the details of the badge (the materials type and the dimensions of the chip, the card, the badge and the filters) and the set-up of the experiment (the source distance and the energies). In comparison with Obryk’s work, the simulation code yielded the mean deviation of 0.59%. For the experimental work, the simulated Hp(10) curves obtained were quite similar and comparable and a mean deviation of 13.96% was obtained. As both 0.59% and 13.96% deviations are within the acceptable limit of ±25%, it was concluded that a satisfactory level of accuracy has been achieved by the developed simulation code and the selection materials and physics processes that have been adapted in the code were correct. Sources of uncertainty that has contributed to this deviation are discussed.